Current Understanding of Circulating Biomarkers in Pulmonary Hypertension Due to Left Heart Disease - Todd, Noah; Lai, Yen-Chun (Frontiers in Medicine, 2020)
Pulmonary hypertension due to left heart disease (PH-LHD; Group 2), especially in the setting of heart failure with preserved ejection fraction (HFpEF), is the most frequent cause of PH. Despite its prevalence, no effective therapies for PH-LHD are available at present. This is largely due to the lack of a concise definition for hemodynamic phenotyping, existence of significant gaps in the understanding of the underlying pathology and the impact of associated comorbidities, as well as the absence of specific biomarkers which can aid in the early diagnosis and management of this challenging syndrome. Currently, B-type natriuretic peptide (BNP) and N-terminal proBNP (NT-proBNP) are guideline-recommended biomarkers for the diagnosis and prognosis of heart failure (HF) and PH. Endothelin-1 (ET-1), vascular endothelial growth factor-D (VEGF-D) and microRNA-206 have also been recently identified as new potential circulating biomarkers for patients with PH-LHD. In this review, we aim to present the current state of knowledge of circulating biomarkers which can be used to guide future research towards diagnosis, refine specific patient phenotype and develop therapeutic approaches for PH-LHD, with a particular focus on PH-HFpEF. Potential circulating biomarkers identified in pre-clinical models of PH-LHD are also summarized here.